Environmental philosophy in Asian traditions of thought - Callicott, J. Baird; McRae, James, 1976-; James, George Alfred, 1946- (State University of New York Press, 2014)
"Leading scholars draw from the Indian, Chinese, and Japanese traditions of thought to provide a normative framework that can address the environmental challenges being faced in the twenty-first century. Hindu, Buddhist, Confucian, and Daoist approaches are considered along with those of Zen, Japanese Confucianism, and the contemporary philosophy of the Kyoto School. An investigation of the environmental philosophy in these Asian traditions not only challenges Western assumptions, but also provides and understanding of Asian philosophy, religion, and culture that informs contemporary environmental law and policy."--Back cover